SOLUÇÃO DE INVETARIO DE HARDWARE, SOFTWARE E SUPORTE REMOTO - BENATTI, FERNANDO H.; FORNASIER, CLÁUDIO S.; BENATTI, DENIS V.; JR, HELMUTH G.; BENEDETTI, VERA L. L. (Salão do Conhecimento, 2013)
Resumo